Some Analogies of the Banach Contraction Principle in Fuzzy Modular Spaces - Kittipong Wongkum; Parin Chaipunya; Poom Kumam (The Scientific World Journal)
We established some theorems under the aim of deriving variants of the Banach contraction principle, using the classes of inner contractions and outer contractions, on the structure of fuzzy modular spaces.